The impact of blood flow restriction training combined with low-load resistance training on the risk of falls in patients with knee osteoarthritis in China: a single-centre, two-arm, single-blind, parallel randomised controlled trial protocol - Yuping Zhang; Xiaoting Chen; Qiuxiang Lin; DeBiao Yu; Tianxiang Lu; Jiawei Qin; Fuchun Wu (BMJ Open)
Introduction Patients with knee osteoarthritis are at a higher risk of falls compared to healthy individuals, thereby increasing the likelihood of accidental injury. Resistance training is an important strategy for managing knee osteoarthritis. Although some studies suggest that blood flow restriction training combined with low-load resistance training (LL-BFRT) is a beneficial treatment approach, its effect on fall risk and balance function in patients with knee osteoarthritis remains unclear. We aim to conduct a randomised controlled trial to assess the effectiveness of combined training in reducing fall risk and improving function in patients with knee osteoarthritis.Methods and analysis We will conduct a single-blind pilot randomised controlled trial involving patients with knee osteoarthritis. 98 patients will be randomly assigned to either the LL-BFRT group or the low-load resistance training (LL-RT) group, with a 1:1 allocation ratio. Both groups will undergo a 4-week intervention. Follow-up assessments will be conducted at baseline, 4 weeks, 16 weeks, 28 weeks and 52 weeks. The primary outcome will be the measurement of the fall risk stability index and overall stability index using the Biodex Balance System. Secondary outcomes include the Numerical Rating Scale, the Western Ontario and McMaster Universities Osteoarthritis Index, the 30 s Chair Stand Test, proprioception testing, the Timed Up and Go Test, the Short Form-36 scores, compliance and adverse events. Intention-to-treat principles will be applied in data analysis.Ethics and dissemination This study has been approved by the Ethics Review Committee of the First Hospital of Quanzhou Affiliated Fujian Medical University (2024-K161). The results of the study will be disseminated through peer-reviewed publications.Trial registration number ChiCTR2400087829.